Las destrezas orales en el aula de ELE: situación actual de las competencias comunicativas. /Gabino Boquete. - Boquete, Gabino.
Following the introduction of communicative strategies, current models of language teaching afford a crucial role to oral skills in the classroom. This paper shows the very real importance given to the use of oral skills in the language teaming process. We carried out research with students and teachers of Spanish at the University of Alcalá, focusing on their preferences and use of different communicative competences. Oral skills are the best valued by students of Spanish and native teachers of this language; by contrast nonnative teachers prefer teaching grammar and writing skills. Likewise, there is no correspondence, in the case of international students, between what they would like to study and what they have actually studied in their home country.